Tinjauan Yuridis Tentang Proses Penyelesaian Perkara Wanprestasi Dalam Perjanjian Pembagian Harta Warisan (Studi Kasus Di Pengadilan Negeri Surakarta) - Rahmadhani, Ganes Agriftya, Nuswardhani, S.H.,S.U, Septarina Budiwati, S.H., M.H (2016)
The objective of this study is to determine the legal responsibilities if one of the party is in default under the agreement the division of the inheritance, to know the judge decisive the proof, to know the consideration of judges in decisions on cases of default in sharing agreement inheritace. The Method uses normative approach and qualitative approach. Kind of descriptive research. Data analysis method used by the author is qualitative approach. In legal responsibilities if one party is default in the agreement sharing the inheritance with their basics in the provisions of article 1236 of the criminal code, the parties felt disadvantage by their sharing agreements inheritance because the other refused the default, then the party who feels disadvantage can demand accountability for what he's to reimburse costs and losses. To demand legal responsibility can be filled to the district court. So in the end the judges have finished checking and verdicting that declared the defendant has made the default against the plaintiffs above sharing agreements or solving Nuriah inheritance in the form of a piece of land 2,139 m² and everything that lives on it as written in SHM no 234, located at Jalan pasar Legi, Kestalan Village, Banjarsari District, municipality of Surakarta, Central Java Province. The judge in determining the evidence and the decision on the case of default in sharing agreement inheritance that the judges had obtained legal facts which is used as a conclusion proving the point that the plaintiff was able to prove the acts of the defendant in default, while the other side of defendant couldn't prove the rebuttal arguments.